Succeeding in Innovation: Key Insights on the Role of R&D and Technological Acquisition Drawn from Company Data - Andrea Conte; Marco Vivarelli (Institute for the Study of Labor (IZA), 2013)
This paper discusses the relationship between a company's investment in innovation and its success in introducing new product and/or process innovations. In doing so, this analysis departs from the standard approach which puts forward a homogenous R&D-based knowledge production function by introducing different types of innovation investments (R&D and technology acquisition) for different sets of companies. Using the Community Innovation Survey (CIS) dataset comprising more than 3000 Italian manufacturing companies, the econometric analysis adopts a set of techniques which allows to control for the sample selection, endogeneity and simultaneity problems which arise when dealing with CIS data. The main findings are summarised as follows: (1) beyond the acknowledged effect of R&D in increasing the probability of success of product innovation, a larger-than-expected role is played by technology acquisition in the innovation process; (2) the relative importance of R&D and technology acquisition varies significantly across different types of companies where crucial dimensions of analysis are company size and the technological domain of a sector.
Keywords: O31; 330; R&D; product innovation; process innovation; embodied technical change; sample selection; SUR; community innovation survey